Membranes for membrane reactors : preparation, optimization, and selection - Basile, Angelo (Angelo Bruno).; Gallucci, Fausto (Chichester, West Sussex : John Wiley & Sons, 2011)
'Membranes for Membrane Reactors Preparation, Optimization and Selection Editors Angelo Basile Institute of Membrane Technology, ITM-CNR c/o University of Calabria, Rende (CS), Italy and Fausto Gallucci Faculty of Chemical Engineering and Chemistry, Eindhoven University of Technology, Eindhoven, The Netherlands A membrane reactor is a device for simultaneously performing a reaction and a membrane-based separation in the same physical device. Therefore, the membrane not only plays the role of a separator, but also takes place in the reaction itself. This text covers, in detail, the preparation and characterisation of all types of membranes used in membranes reactors. Each membrane synthesis process used by membranologists is explained by well known scientists in their specific research field. The book opens with an exhaustive review and introduction to membrane reactors, introducing the recent advances in this field. The following chapters concern the preparation of both organic and inorganic, and in both cases, a deep analysis of all the techniques used to prepare membrane are presented and discussed. A brief historical introduction for each technique is also included, followed by a complete description of the technique as well as the main results presented in the international specialized literature. In order to give to the reader a summary look to the overall work, a conclusive chapter is included for collecting all the information presented in the previous chapters. This text is intended for PhD students, chemical engineers, environmental engineers, materials science experts, biologists, researchers and is an ideal resource to those who intend to study and investigate membrane reactors'--
'The discovery of new membrane materials was the key factor for increasing the application of the membrane in the catalysis field'--
Includes bibliographical references and index.
Keywords: Membrane reactors